Hubungan Tingkat Anxiety dengan Derajat Insomnia pada Mahasiswa Akhir ITSK RS dr. Soepraoen Malang - Alfianita, Nanda; Permata, Agung; Mardianto, Rudy (Innovative: Journal Of Social Science Research, 2024)
Background: Anxiety disorder is a common mental disorder that greatly affects sufferers. In the case of students themselves, risk factors for anxiety can be cognitive factors related to how students perceive results and goals which are also related to anxiety, and affective factors can influence test anxiety on students or the feelings they feel before the test takes place will increase their anxiety. Objective: to ascertain final student' levels of anxiety and degree of insomnia at ITSK RS Dr. Soepraoen, Malang. Methods: This study is an observational design that assesses the relationships of the levels of anxiety and the degree of insomnia in final students. To acquire samples, the systematic random sampling technique was applied. The inclusion criteria were met by 102 final semester students. The Depression Anxiety Stress Scales (DASS) were used to collect data. and Insomnia Severity Index (ISI) questionnaires. Result: Research describes 72.5% of final year students with anxiety and 53.9% of final year students experiencing insomnia disorders. Rank analysis test (Sig <001; correlation coefficient 0.617). Conclusion: The test shows that there is a strong relationships of anxiety and the incidence of insomnia in final students.